Re-assessment of Taxonomy and Host Range of Colletotrichum from Korea: Focus on the C. boninense, C. spaethianum Species Complexes, and Related Taxa - Thao, Le Dinh; Choi, Hyorim; Kang, Donghun; Mageswari, Anbazhagan; Lee, Jae Sung; Lee, Daseul; Choi, In-Young; Shin, Hyeon-Dong; Hong, Seung-Beom (The plant pathology journal, 2025)
Colletotrichum species are commonly known as important phytopathogens causing anthracnose in Korea and worldwide, with a diverse range of host plants. Colletotrichum isolates preserved in the Korean Agricultural Culture Collection (KACC) are important resources for scientific research as well as anthracnose disease management strategies in Korea. Many Colletotrichum isolates in KACC had been identified using morphological characteristics and their host plants by depositors, this could lead to inaccurate species names. In this study, 38 KACC isolates were, therefore, re-identified as 13 known species (C. boninense, C. caudasporum, C. coccodes, C. echinochloae, C. karsti, C. liriopes, C. nigrum, C. sansevieriae, C. spaethianum, C. sublineola, C. sydowii, C. truncatum, and C. zhaoqingense) and a new species candidate, based on multi-locus sequence analyses of the nuclear ribosomal internal transcribed spacers, glyceraldehyde-3-phosphate dehydrogenase (gapdh), chitin synthase 1 (chs-1), histone-3 (his3), actin (act), beta-tubulin 2 (tub2), and manganese-superoxide dismutase (sod2). Of these, C. caudasporum, C. echinochloae, and C. zhaoqingense are unrecorded species in Korea. The results also revealed 16 new host-fungus combinations in Korea, including 13 new combinations worldwide. However, the pathogenicity of the fungal species in this work on their hosts was not confirmed.